Fairness in allocation decisions: does type of resource and relationship matter? - Hassan, Arif; Ahmed, Mohammad (SpringerLink, 2019)
The study, conducted in Malaysia, examined the role of recipient–allocator relationship in perceived choice of resource allocation norms (equity, equality, and need) on two types of resources (money and favour) and the degree to which they were considered fair. Subjects responded to vignettes that described a resource to be allocated by an allocator between a needy and a meritorious employee. Recipients relationship status in the vignettes indicated that one of the two was the brother of the allocator who was either meritorious or needy. In the control group, no relationship characteristic of the recipient was stated. Results indicated that equality was the fairest and preferred norm of justice. No significant difference was obtained among the perceived norm and fairness in all but one situation distribution of loan). The results are discussed in relation to the subjects’ cognitive strategy and collectivistic values.